Natural woody species biodiversity after Cypress (Cupressus sempervirens var. horizontalis) reforestation in Hyrcanian Forest, North of Iran - LEILA VATANI; SEYED MOSEH HOSSEINI; MOSLEM AKBARINIA; SAEED SHAMSI (Biodiversitas Journal of Biological Diversity, 2017)
Vatani L, Hosseini SM, Akbarinia M, Shamsi S. 2017. Natural woody species biodiversity after Cypress (Cupressus sempervirens var. horizontalis) reforestation in Hyrcanian Forest, North Iran. Biodiversitas 18: 689-695. The present study was conducted to investigate the impact of Cypress (Cupressus sempervirens var. horizontalis) reforestation (15 years old ) on woody species diversity comparison natural Hyrcanian forests. 9 sample plots with 20 Ã— 20m area were taken in each stand by a random systemic statistical method and also control area, then natural regeneration number of woody species were measured. Shannon-Wiener for diversity index, Mechanic for richness index and Simpson for evenness index were calculated to evaluate species biodiversity, using Ecological Methodology and SPSS software. The results showed that sixteen tree and shrub species were appeared in Cypress understory naturally, that some of the species were rare. There was no significant difference between the diversity and richness index obtained for Cypress reforestation and natural forest. Regarding the rate of evenness, only in one area was found a significant difference was observed between Cypress reforestation and natural forest that in reforestation was more than natural forest (p<0.05). Regarding the results obtained on the study, Cypress reforestation did not reduce the woody plant biodiversity until the age of fifteen years old and findings of this investigation suggested that the conditions under the Cypress canopy might be suitable for the presence of some woody species, 15 years after reforestation